2007
DOI: 10.1007/s10517-007-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental intravenous cell therapy of acute and chronic renal failure

Abstract: The therapeutic effect of intravenous injection of human fetal bone marrow mesenchymal stem cells or summary culture of kidney cells were studied on models of chronic or acute renal failure in outbred albino rats. Both cell types promoted improvement and normalization of the renal function in rats with stable chronic renal insufficiency (2 weeks after kidney cell injection, 1 month after bone marrow mesenchymal stem cell injection). Renal function remained normal or subnormal during the delayed period (3-3.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
(16 reference statements)
0
5
0
2
Order By: Relevance
“…In a rodent model, chronic renal disease was established by heminephrectomy and ischemia to the intact kidney. 11 Injection of a heterogeneous mixture of human fetal kidney cells, containing embryonic tubular cells, via the vena cava into rats with established disease led to transient improvement of all functional parameters. The recovery observed in rats receiving fetal kidney cells was more rapid in the context of chronic disease state than that observed in rats receiving bone marrow-derived mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a rodent model, chronic renal disease was established by heminephrectomy and ischemia to the intact kidney. 11 Injection of a heterogeneous mixture of human fetal kidney cells, containing embryonic tubular cells, via the vena cava into rats with established disease led to transient improvement of all functional parameters. The recovery observed in rats receiving fetal kidney cells was more rapid in the context of chronic disease state than that observed in rats receiving bone marrow-derived mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of MSC application in rodent model of induced CKD reported renal function improvement through intrarenal fibrosis and inflammation reduction (Cavaglieri et al., ; Kirpatovskii et al., ; Lee et al., ; Ninichuk et al., ; Semedo et al., ; Villanueva et al., , ; Wang, He, Pei, & Zhao, ). Our findings are as satisfactory as those found in rodent model of induced CKD; however, despite using MSCs with similar therapeutic potential, findings in previous studies in cats with naturally occurring CKD did not report significant variations (Quimby et al., , , ).…”
Section: Discussionmentioning
confidence: 97%
“…The potential MSC therapy for CKD has been reported in numerous studies of induced CKD in rodents (Cavaglieri, Martini, Sogayar, & Noronha, ; Kirpatovskii et al., ; Lee et al., ; Ninichuk et al., ; Semedo et al., ; Villanueva et al., , ). These studies have shown a decrease and stabilization of the clinical condition, evidenced by renal function improvement and by inflammation and renal fibrosis reduction (Cavaglieri et al., ; Lee et al., ; Ninichuk et al., ; Semedo et al., ; Villanueva et al., ).…”
Section: Introductionmentioning
confidence: 95%
“…10 5 stem cells and demonstrated that a small cell number with oxytocin pretreatment could be enough to exert its therapeutic effect for 4 weeks in a myocardial infarction rat model. Antifibrotic, anti-inflammatory, and proangiogenic effects are well-known therapeutic mechanisms of stem cells in ischemic-injured organs [Kirpatovskii et al, 2007;Segers and Lee, 2008]. MSCs differentiated into myogenic, endothelial, and smooth muscle cells in the infarcted reveal whether the transient induction might trigger an unknown signaling cascade.…”
Section: Discussionmentioning
confidence: 99%